Survey of gut microbial biogeography and their functional niche in the grow-finishing swine of ordinary feeding - Cao, Lili; Guo, Wei; Yang, Shiyu; Ahmad, Anum Ali; Dong, Yuntao; Gong, Cen; Wang, Shuoqi; Yang, Xuemin; Cheng, Zhentao; Yan, Zhihong; Wang, Weiwei (Frontiers in Microbiology, 2025)
BackgroundSwine represent one of the most economically significant livestock worldwide, and their intestinal microbial communities are crucial for maintaining physiological development and regulating host metabolism. While extensive research has focused on the fecal microbiota of swine, investigations into microbial communities across different intestinal segments remain limited.ObjectiveThis study aims to elucidate the intestinal microbiota of swine by analyzing luminal contents from different intestinal segments, including the duodenum, jejunum, ileum, cecum, and colon.MethodsWe employed 16S rRNA sequencing to explore the diversity and structure of gut microbial biogeography, microbial functional niches, and their associated pathways.ResultsOur findings reveal significantly lower microbial richness and diversity in the small intestine (duodenum, jejunum, and ileum) compared to the large intestine (cecum and colon) (p < 0.05). At the phylum level, Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes were the dominant phyla, collectively accounting for over 90% of the total sequences. In the small intestine, Proteobacteria (4.76–34.2%), Actinobacteria, and Fusobacteriota were more abundant, whereas in the large intestine, Firmicutes (89.8–90.4%) was predominated. At the genus level, Fusobacterium, Corynebacterium, Rothia, Bradyrhizobium, and Brevundimonas were predominant in duodenum. Romboutsia, Clostridium_sensu_stricto_1, Terrisporobacter, and Jeotgalicoccus demonstrated greater abundances in the jejunum and ileum. Oscillospiraceae_UCG-005 in the cecum and Christensenellaceae_R-7_group in the colon were more abundant with 16.4 and 20.2% relative abundances, respectively. The specialists detected from the duodenum to the colon were all the predominant genera in each intestinal segment with relatively higher relative abundance. For instance, Romboutsia (3.06–36.1%), Clostridium_sensu_stricto_1 (5.31–18.6%), and Terrisporobacter (0.849–5.72%) were dominant genera and specialists in the small intestine, associated with enriched pathways of Amino acid metabolism and Lipid metabolism. Conversely, Oscillospiraceae_UCG-005 (16.4%, 4.06%) and Christensenellaceae_R-7_group (5.44%, 20.2%) are predominant genera and specialists within the large intestine, linked to pathways involved in Glycan biosynthesis and metabolism pathway, as well as the Biosynthesis of other secondary metabolites.ConclusionThese highlight the importance of genus specialists compared to genus generalists. The findings provide essential data for assessing the role of the intestinal microbiome in maintaining and enhancing swine health and productivity, offering fundamental guidance for further exploration of host-microbe interaction mechanisms and regulatory pathways.